Farmers’ Preferences for Tree Species on Agroforestry System in Ijebu North Local Government Area, Ogun State, Nigeria (2012)
This study was conducted to generate information on tree species farmers are willing to retain or plant on then- farms; the benefits they derive from the trees and the traditional management practices used for such trees in Ijebu North Local Government Area of Ogun State, in southwestern Nigeria, Multistage sampling technique was used to collect data on the tree species preferred by farmers, the benefits derived from the trees and the management practices used for such trees. A structured questionnaire was administered and data were analyzed using simple descriptive statistics. Farmers retain 72 tree species on their farms based on their knowledge and socio economic needs. They retain and plant fruit trees (17%), timber trees (18%), fuelwood (1%), and medicinal trees (1%). Sixty three percent (63%) of the farmers retain all the types of tree species on their farms as scattered on-farm trees due to the benefits they derive from them. The benefits include: food (88.8%), firewood (78.8%), fruits (95.6%), shades (91.9%), traditional medicine (94.4%), income generation (98.8%) and other environmental services (31.4%). On- farm trees are regenerated or sown directly on the field. Pruning and coppicing are the management practices applied.